New Headway Advanced: Workbook with key - Soars L. Liz (New York, Oxford University Press, 2008)
New Headway ancedThe world's most trusted English courseNew Headway is the course teachers and learners can rely on. Why? An authoritative integrated syllabus, motivating topics, and clearly focused tasks, combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning.Tried and tested all over the world, it's probably the most popular course ever written!what's in New Headway Advanced Workbook? Thorough practice of the Student's Book grammar syllabusRevision of key vocabulary areas, and vocabulary extensionWork on phrasal verbs, synonyms, and collocation. Listening and pronunciation exercises for self-study.